2018
DOI: 10.1182/blood-2017-10-813931
|View full text |Cite
|
Sign up to set email alerts
|

Novel role of prostate apoptosis response-4 tumor suppressor in B-cell chronic lymphocytic leukemia

Abstract: Prostate apoptosis response-4 (Par-4), a proapoptotic tumor suppressor protein, is downregulated in many cancers including renal cell carcinoma, glioblastoma, endometrial, and breast cancer. Par-4 induces apoptosis selectively in various types of cancer cells but not normal cells. We found that chronic lymphocytic leukemia (CLL) cells from human patients and from Eµ-Tcl1 mice constitutively express Par-4 in greater amounts than normal B-1 or B-2 cells. Interestingly, knockdown of Par-4 in human CLL-derived Mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Evaluating PAWR expression provided a feasible approach to predict survival and drug responsiveness of ovarian cancer patients by simply performing immunohistochemical staining, which is convenient and cost-effective. Consistent with result for some other tissues [ 13 , 15 ], PAWR was expressed in the cytoplasm in cells of normal fallopian tubes, while there was both cytoplasmic and nuclear expression of PAWR in cancer samples. PAWR can also be secreted spontaneously by normal and cancer cells in culture [ 38 ], providing the possibility of detection by non-invasive liquid biopsy.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Evaluating PAWR expression provided a feasible approach to predict survival and drug responsiveness of ovarian cancer patients by simply performing immunohistochemical staining, which is convenient and cost-effective. Consistent with result for some other tissues [ 13 , 15 ], PAWR was expressed in the cytoplasm in cells of normal fallopian tubes, while there was both cytoplasmic and nuclear expression of PAWR in cancer samples. PAWR can also be secreted spontaneously by normal and cancer cells in culture [ 38 ], providing the possibility of detection by non-invasive liquid biopsy.…”
Section: Discussionsupporting
confidence: 89%
“…3 c). The PTEN/PI3K/AKT signaling pathway, implicated in cell proliferation, apoptosis, metastasis, and chemo-resistance of ovarian cancer, has been reported to correlate with PAWR [ 4 , 15 , 32 ]. Using GEPIA, we found positive correlations between PAWR and the three hub genes of this axis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here We recently reported that whole-organism knockout Pawr 2/2 3 TCL1 mice display delayed disease development and improved survival compared with Pawr 1/1 3 TCL1 mice. 35 This is ascribed to upregulated p21 expression in leukemic B cells and decreased proliferation resulting from Par-4 knockout. Interestingly, the Par-4 overexpression in leukemic B cells reported here also results in delayed disease progression, suggesting roles for Par-4 in both the leukemia cells and the tumor microenvironment during disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, PAR-4 inhibits the transcriptional activity of the key survival factor NFκB, thus preventing the expression of pro-inflammatory and anti-apoptotic genes [5]. In addition, PAR-4 regulates apoptosis of neurodegenerative diseases [6][7][8]. However, there are few studies on the pro-apoptotic protein PAR-4 in the context of chondrocyte death.…”
Section: Introductionmentioning
confidence: 99%